Visible range plasmonic effect produced by aluminium nanoparticles embedded in amorphous silicon. Issue 12 (26th October 2015) - Fantoni, Alessandro; Fernandes, Miguel; Vygranenko, Yury; Louro, Paula; Vieira, Manuela
Abstract: We present results, obtained by means of an analytic study and a numerical simulation, about the resonant condition necessary to produce a Localized Surface Plasmonic Resonance (LSPR) effect at the surface of metal nanospheres embedded in an amorphous silicon matrix. The study is based on a Lorentz dispersive model for a‐Si:H permittivity and a Drude model for the metals. Considering the absorption spectra of a‐Si:H, the best choice for the metal nanoparticles appears to be aluminium, indium or magnesium. No difference has been observed when considering a‐SiC:H. Finite‐difference time‐domain (FDTD) simulation of an Al nanosphere embedded into an amorphous silicon matrix shows an increased scattering radius and the presence of LSPR induced by the metal/semiconductor interaction under green light (560 nm) illumination. Further results include the effect of the nanoparticles shape (nano‐ellipsoids) in controlling the wavelength suitable to produce LSPR. It has been shown that is possible to produce LSPR in the red part of the visible spectrum (the most critical for a‐Si:H solar cells applications in terms of light absorption enhancement) with aluminium nano‐ellipsoids. As an additional results we may conclude that the double Lorentz‐Lorenz model for the optical functions of a‐Si:H is numerically stable in 3D simulations and can be used safely in the FDTD algorithm. A further simulation study is directed to determine an optimal spatial distribution of Al nanoparticles, with variable shapes, capable to enhance light absorption in the red part of the visible spectrum, exploiting light trapping and plasmonic effects. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)